Analytical evaluation of local effects in cylindrical shells testing and design - Guarracino, F. (Проблемы прочности, 2009)
A simple analytical evaluation of apparently anomalous results from tests on circular cylindrical shells that have been observed in the past is provided on the basis of the classical Ritz approach and modified Donnell relationships.